stilPCR increases the effective sequencing length of Illumina targeted next-generation sequencing. - Jason D Limberis; Roland J Nagel; Soumitesh Chakravorty; Dena Block; Scott Dewell; Alina Nalyvayko; Zach Howard; Grant Theron; Rouxjeane Venter; John Z Metcalfe (PLoS ONE)
Identifying pathogens, resistance-conferring mutations, and strain types through targeted amplicon sequencing is an important tool. However, due to the limitations of short read sequencing, many applications require the division of limited clinical samples. Here, we present stilPCR (single-tube Illumina long read PCR), which allows the generation of hemi-nested amplicons in a single tube, with Illumina indexes and adapters, effectively increasing the Illumina read length without increasing the input requirements of reagents or sample. We have successfully utilized stilPCR on clinical sputum from tuberculosis patients to detect drug resistance mutations.